Towards an Interreligious Fiqh: A Study of the Culture-Based Religious Tolerance in the Kaloran Community, Central Java, Indonesia - Sodiqin, Ali; Umroh, Roehana Rofaidatun (Al-Jami'ah Research Centre, 2023)
This paper explores local wisdom in Kaloran, Temanggung, Central Java, Indonesia, with its religious diversity that influences the understanding and practice of their religiosity. The people’s local wisdom is agama ageming aji and sing penting brayan, which becomes the basis for building religious tolerance. It raises the question of how people interpret this philosophy as a guideline for building religious tolerance. What is the dialectic pattern of religion and culture practised by Kaloran Muslims? What is the form of implementation of inter-religious fiqh that manifests religious tolerance? The researchers argue that religion for the Kaloran people is like ageman (clothing), so choosing a religion is an individual’s freedom and rights that somebody must respect. The ultimate purpose of religion is to build social harmony (brayan). In addition, the pattern of religious and cultural dialectics practised by the Muslim Kaloran is in the form of desacralisation and culturalization of religious teachings. The pattern, in turn, encourages the rise of such kind of inter-religious fiqh built by placing religion as a private matter and must go hand in hand with culture as a medium for building tolerance. The Muslim community integrated religion and culture through desacralisation and culturalization.[Tulisan ini membahas kearifan lokal masyarakat Kaloran, Temanggung, Jawa Tengah, Indonesia, dengan keragaman keagamaannya yang mempengaruhi pemahaman dan praktik keberagamaan masyarakat. Mereka memiliki kearifan lokal berupa agama ageming aji dan sing penting brayan sebagai dasar membangun toleransi beragama. Hal ini menimbulkan pertanyaan bagaimana masyarakat memaknai falsafah tersebut sebagai pedoman dalam membangun toleransi beragama? Bagaimana pola dialektika agama dan budaya yang dipraktikkan Muslim Kaloran? Bagaimana bentuk implementasi fikih antar agama yang merupakan perwujudan dari toleransi beragama? Penelitian ini menunjukkan bahwa agama bagi masyarakat Kaloran diibaratkan sebagai ageman (pakaian), sehingga memilih agama adalah kebebasan dan hak individu yang harus dihormati. Tujuan beragama adalah untuk membangun harmoni sosial (brayan). Dengan pemahaman seperti itu, pola dialektika agama dan budaya yang dipraktikkan oleh masyarakat Kaloran berupa desakralisasi dan kulturalisasi ajaran agama terhadap budaya. Pola ini kemudian mendorong munculnya konstruksi fikih antar agama yang dibangun dengan menempatkan agama dalam wilayah privat yang harus berjalan beriringan dengan budaya sebagai media membangun toleransi. Agama dan budaya diintegrasikan melalui pola desakralisasi dan kulturalisasi.